Proceedings of the Fourth ACL-SIGSEM Workshop on Prepositions - SigSem '07 2007
DOI: 10.3115/1654629.1654636
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the productivity of determinerless PPs

Abstract: We determine the productivity of determinerless PPs in German quantitatively, restricting ourselves to the preposition unter. The study is based on two German newspaper corpora, comprising some 210 million words. The problematic construction, i.e. unter followed by a determinerless singular noun occurs some 16.000 times in the corpus. To clarify the empirical productivity of the construction, we apply a productivity measure developed by Baayen (2001) to the syntactic domain by making use of statistical models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 7 publications
(13 reference statements)
1
9
0
3
Order By: Relevance
“…Payne & Huddleston (2002: 409-410) extend this idea from FIXED EXPRESSIONS to FIXED FRAMES for English PNCs. Dömges et al (2007) and Kiss (2007) have shown, however, that the construction is indeed productive, using a quantitative measure to gauge whether new instances of a construction emerge over time.…”
Section: Structural Aspects Of Determiner Omissionmentioning
confidence: 99%
“…Payne & Huddleston (2002: 409-410) extend this idea from FIXED EXPRESSIONS to FIXED FRAMES for English PNCs. Dömges et al (2007) and Kiss (2007) have shown, however, that the construction is indeed productive, using a quantitative measure to gauge whether new instances of a construction emerge over time.…”
Section: Structural Aspects Of Determiner Omissionmentioning
confidence: 99%
“…PNCs present an anomaly in the grammar: they violate the rule that countable singular nouns have to appear with a determiner. For some time, PNCs have been treated as exceptions, but recent research has shown that they are indeed productive and no more idiomatic than other phrasal combinations (Stvan 1998;Baldwin et al 2006 for English;Dömges et al 2007;Kiss 2007 for German).…”
Section: Preposition Senses and Preposition-noun Combinationsmentioning
confidence: 99%
“…Diese Feststellung soll aber nicht genügen. Basierend auf dem morphologischen Produktivitätsmaß P aus Baayen (2001) und dessen Verallgemeinerung für syntaktische Kontexte in Evert (2004) legen Dömges et al (2007) eine quantitative Analyse der Produktivität von PNKen mit unter vor, aus der hervorgeht, dass es sich bei PNKen um regelhafte Kombinationen handelt. Ohne die technischen Details dieser Analyse hier zu diskutieren, kann der Ansatz wie folgt zusammengefasst werden: Wenn man davon ausgehen würde, dass eine syntaktische Kombination tatsächlich eine aufzählbare Ausnahme ist, dann müsste es auch endlich viele Instanzen dieser Ausnahme geben.…”
Section: Das Problem Der Zählbarkeitunclassified
“…Diese Annahme kann nun von beobachteten Daten auf nicht beobachtete Daten, also von bereits sehr umfangreichen empirischen Korpora auf wesentlich umfangreichere nicht beobachtete Korpora übertragen werden, wenn man so genannte LNRE-Modelle ("large number o f rare events", Baayen 2001) zur Vorhersage nicht beobachteter Daten verwendet. Dömges et al (2007) haben gezeigt, dass das plausibelste Modell für u n teA Substantiv dasjenige Modell ist, das unendlich viele Instanzen dieser Kombination vorhersagt. Somit ist die Kombination regelhaft, auch der Weg über die Ausnahme ist verbaut.…”
Section: Das Problem Der Zählbarkeitunclassified
See 1 more Smart Citation